Non Cognitive factors and Economic Conditions of Individuals working in Informal sector : A systematic review. - Lavish Chugh (International journal of economic perspectives, 2022)
Poverty has become inseparable part of our society. even in developed nations their are people who cannot afford basic facilities, required for survival. researchers have tried to find the reasons behind this severe problem. And now the exploration is not limited to the field of economy, but is studied in various science branches including Psychology. This study is also an attempt to explore the possible causes of poverty. In this review paper we are going to focus upon effect of some non cognitive factors upon real life economic achievements, in the non-formal sectors. According to ACT “Cognitive skills involve conscious intellectual effort, such as thinking, reasoning, or remembering. ...Non-cognitive or “soft skills” are related to motivation, integrity, and interpersonal interaction.” Previous researches support the hypothesis - non cognitive factors like locus of control, conscientiousness and self esteem effect or predict significantly sorting of jobs (Heckman, Stixrud and Urzua, 2006), (Barrick and Mount, 1991; Ham, Junankar and Wells 2009). But there is scope of further research in field of non cognitive factors responsible for keeping someone from fulfilling bare necessities of life.